Nurse Management of Hypertension in Rural Western Kenya: Implementation Research to Optimize Delivery - Vedanthan, Rajesh (2013)
BACKGROUND: Hypertension is the leading global risk factor for mortality. Hypertension treatment and control rates are low worldwide, and insufficient human resource capacity is among the contributing factors. Thus, a critical component of hypertension management is to develop novel and effective solutions to the human resources challenge. One potential solution is task redistribution and nurse management of hypertension in these settings. METHODS: This study investigates whether nurses can effectively reduce blood pressure in hypertensive patients in rural western Kenya and, by extension, throughout sub-Saharan Africa. An initial phase of qualitative inquiry will assess facilitators and barriers of nurse management of hypertension. In addition, we will perform usability and feasibility testing of a novel, electronic tablet-based integrated decision support and record-keeping tool for the nurses. An impact evaluation of a pilot program for nurse-based management of hypertension will be performed. Finally, a needs-based workforce estimation model will be utilized to estimate the nurse workforce requirements for stable, long-term treatment of hypertension throughout western Kenya. RESULTS: The primary outcome measure of the impact evaluation will be the change in systolic blood pressure of hypertensive individuals assigned to nurse-based management after one year of follow-up. The workforce estimation modeling output will be full-time equivalents of nurses. CONCLUSIONS: This study will provide evidence regarding the effectiveness of strategies to optimize task redistribution and nurse-based management of hypertension that can be applicable to non-communicable disease management in low- and middle-income countries.